2009
DOI: 10.1007/s12020-009-9269-9
|View full text |Cite
|
Sign up to set email alerts
|

11β-hydroxysteroid dehydrogenase type-2 and type-1 (11β-HSD2 and 11β-HSD1) and 5β-reductase activities in the pathogenia of essential hypertension

Abstract: Cortisol availability is modulated by several enzymes: 11β-HSD2, which transforms cortisol (F) to cortisone (E) and 11β-HSD1 which predominantly converts inactive E to active F. Additionally, the A-ring reductases (5α- and 5β-reductase) inactivate cortisol (together with 3α-HSD) to tetrahydrometabolites: 5αTHF, 5βTHF, and THE. The aim was to assess 11β-HSD2, 11β-HSD1, and 5β-reductase activity in hypertensive patients. Free urinary F, E, THF, and THE were measured by HPLC-MS/MS in 102 essential hypertensive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 61 publications
3
26
1
Order By: Relevance
“…PRA was determined as described previously. 19 In accordance with our recently reported reference values for the pediatric population, 18 we consider SA level values Ͼ17.7 ng/dL (491.7 pmol/L) to be high, PRA Ͻ0.5 ng/mL per hour to be suppressed (equal to the third percentile in Chilean normotensive healthy pediatric population), and ARR levels values Ͼ10 to be high. 18 In our Chilean hypertensive adult population, the ARR level is considered high when it exceeds 25, 9 and SA is considered high when it exceeds 16 ng/dL.…”
Section: Subjectssupporting
confidence: 72%
“…PRA was determined as described previously. 19 In accordance with our recently reported reference values for the pediatric population, 18 we consider SA level values Ͼ17.7 ng/dL (491.7 pmol/L) to be high, PRA Ͻ0.5 ng/mL per hour to be suppressed (equal to the third percentile in Chilean normotensive healthy pediatric population), and ARR levels values Ͼ10 to be high. 18 In our Chilean hypertensive adult population, the ARR level is considered high when it exceeds 25, 9 and SA is considered high when it exceeds 16 ng/dL.…”
Section: Subjectssupporting
confidence: 72%
“…Cortisol and 11 -HSDs have been implicated in hypertension (Anagnostis et al, 2009;Andrews et al, 2003;Campino et al, 2010;Cicala & Mantero, 2010;Edwards et al, 1988;Ferrari, 2010;Franks et al, 2004;Funder et al, 1988;Gathercole & Stewart, 2010;Y. Liu et al, 2008;Malavasi et al, 2010;Millis, 2011;Monder et al, 1989;Morales et al, 2008;Mune et al, 1995;Palermo et al, 2004;Paterson et al, 2004;Quinkler & Stewart, 2003;Raff & Findling, 2003;Stewart et al, 1996;Walker & Andrew, 2006;Walker et al, 1993;Wallerath et al, 1999;White et al, 1997).…”
Section: β-Hsd1 and Hypertensionmentioning
confidence: 99%
“…essential hypertension (Soro et al, 1995;Walker et al, 1993) and 'salt-sensitive' hypertension (Lovati et al, 1999)] (Bailey et al, 2008;Cooper & Stewart, 2009;Henschkowski et al, 2008). Campino et al reported a high percentage of alterations in the cortisol metabolism at the pre-receptor level in hypertensive patients, previously misclassified as having essential hypertension, where 18% of the patients present reduced 11 -HSD2 activity or imbalance of 11 -HSD1 activity in comparison to 11 -HSD2 (Campino et al, 2010). As referred above, hypertension is induced in mice genetically modified to overexpress 11 -HSD1 either in the liver or AT Paterson et al, 2004).…”
Section: β-Hsd1 and Hypertensionmentioning
confidence: 99%
“…1) play different roles in human physiology and several pathological conditions [1,2]. Cortisol deficiency has been reported in patients with Addison's syndrome leading to hypotension, while excess cortisol is observed in Cushing's syndrome and determined by the onset of hypertension [3].…”
Section: Introductionmentioning
confidence: 99%